Development of a real-time recombinase polymerase amplification assay for rapid detection of Salmonella in powdered infant formula. (March 2020) - Hong, Hanlu; Sun, Chongzhen; Wei, Shuang; Sun, Xia; Mutukumira, Anthony; Wu, Xiyang
Abstract: Salmonella is a foodborne pathogen that may cause serious neonatal disease. In this study, an isothermal real-time recombinase polymerase amplification (RPA) was established to detect Salmonella at 37 °C within 20 min, with the detection sensitivity of 10 3 cfu mL −1 in pure culture. In food applications using powdered infant formula (PIF), the detection limit of Salmonella using this assay was 2 × 10 3 cfu mL −1 without a pre-enrichment procedure. When PIF was spiked with Salmonella at 0.1, 1 and 10 cfu mL −1 and enriched at 37 °C, results showed that this assay can detect Salmonella at initial inoculation level of 0.1 cfu mL −1 in PIF after 8 h pre-enrichment. This real-time RPA assay was considerably faster than qPCR and exhibited no losses in detection sensitivity and specificity, therefore it was suitable for on-site detection, especially in resource-poor environments.